Pesan Moral Islam dalam Film Iqro My Universe - Yati, Edra Adha (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2022)
Film Iqro My Universe is an Islamic nuanced film that has many moral messages, one of which is being serious about achieving your dreams. The purpose of this study was to determine the meaning of denotation, connotation, and myths of Islamic moral messages contained in the film Iqro My Universe. The research method used in this research is descriptive qualitative. The theory used in analyzing this data is using Roland Barthes' semiotic theory analysis. Based on the results of the study, it was concluded that the meaning of denotation in each scene and dialogue of the characters has an explanation that really visualizes everyday life in a family. The connotations in this film include helping each other, being devoted to both parents, having aspirations with the intention of seeking God's pleasure. The meaning of myth is based on the verses of the Qur'an and the culture of the Islamic community in living daily life. Keywords: Message of Moral; Film; Semiotics; Islam.